DESCRIPTION OF THE QUALITY OF THE TEAM'S PROFESSIONAL NURSING CARE MODEL (MAKP) IMPLEMENTATION - Kristina, Yuyun (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. The Professional Nursing Care Model (hereinafter abbreviated as MAKP) is a system (structure, processes, and values) that allows professional nurses to manage the provision of nursing care including the environment to support the provision of such care. Good nursing services are services that include comprehensive nursing care services and in the provision of nursing care, there are things that support the success of providing services, one of which is MAKP. This study aims to determine the relationship of nursing care models to the performance of nursing services. Method. The literature study method used secondary data from previous research results which are published journals, which are in accordance with the criteria set by the research, namely by having systematic inclusion and exclusion criteria and searching using the Online Database. Result&Analysis. It is found two articles that explain the relationship between the application of the nursing care model team and the job satisfaction of nurses. It is found three articles that explain the relationship between the application of the nursing care model team and the performance of nursing services. Discussion. There is an influence of the professional nursing care model (MAKP) team on the performance of nursing services.